ABDOMINAL HEMORRHAGE IN CASE OF CATATRAUMA - A. M. Khadzhibaev; P. K. Sultanov (Вестник хирургии имени И.И. Грекова)
The results of diagnostic and treatment were analyzed in 111 victims with abdominal multitrauma at the period from 2010 to 2013. Abdominal traumas were diagnosed on the basis of instrumental investigations and laparascopic data. Combined injuries were often observed in 3-5 areas. The abdominal hemorrhages were in 66 patients as a result of injury of the parenchymatous organs. Diagnostic value of clinical symptoms wasn’t more than 45,9% in abdominal catatrauma, though in case of plan radiography it was from 41,2% to 66,4% and in case of ultrasound study - 91,6%. The laparotomy was performed for 28 patients. The laparoscopy was applied in 66 cases. However, there were revealed the cases of continuing bleeding in 31 patients and because of these complications, the operations were converted to laparotomy in 27 cases. Different variants of laparoscopic coagulation were performed on 4 patients. The rate of lethality consisted of 27%. The authors proposed an algorithm of treatment of the patients with closed abdominal injury on the basis of score assessment of hemoperitoneum (according to USS), which allowed significant rise of treatment efficacy, decrease the rate of postoperative complications and lethality.